RETRACTED: Information model of green building research in the Arctic: methodological aspects - Kuzmenkov Alexander; Kaychenov Alexander; Karachentseva Iana; Vasileva Zhanna; Buryachenko Svetlana; Voronin Zahar (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001